Constrictive Pericarditis Associated with Marlex Mesh: Two Case Reports - Chen, Robert F. (2001)
Two patients were referred to our hospital with constrictive pericarditis approximately 1 year after undergoing mitral valve repair at another institution. Both repairs had included the use of a pericardial substitute, Marlex mesh, to prevent adhesion and to facilitate possible reoperations. Computed tomography and cardiac catheterization were used to establish the diagnosis of constrictive pericarditis. During surgery, dense, thickened fibrous tissue, the result of a Marlex mesh-related reaction, was found tightly adhered to the epicardium in each of the patients. It appeared that the Marlex mesh, which had been inserted to facilitate reoperation, had contributed to the development of constrictive pericarditis.